Is sales tax included in the price? Consumer inattention and price competition - Oz Shy (Federal Reserve Bank of Atlanta, 2024)
Sales tax is generally not included in the advertised price quoted to consumers in the United States. In contrast, value added taxes (VAT) are embedded into the price in most other countries. This article investigates how the two different pricing structures and consumers' decision-making process affect the intensity of price competition. The two pricing structures yield identical market outcomes with fast-computing consumers who are willing and able to recompute the exact sales tax each time there is a price change. With slow-computing consumers, prices and profits are higher when sellers quote and compete in prices without sales tax. In this case, a model extension with two-stage decision making shows that the entire tax burden is shifted to the consumers when they completely ignore sales tax during their initial search.
Keywords: D43; H29; L13; M3; 330; price competition; price comparisons; sales tax; value added tax; fast and slow-computing consumers; mental accounting; inattention; consumer decision making